Evaluation of serological lateral flow assays for severe acute respiratory syndrome coronavirus-2. - Trombetta, Bianca A.; Kandigian, Savannah E.; Kitchen, Robert R.; Grauwet, Korneel.; Webb, Pia Kivisäkk.; Miller, Glenn A.; Jennings, Charles G.; Jain, Sejal.; Miller, Samara.; Kuo, Yikai.; Sweeney, Thadryan.; Gilboa, Tal.; Norman, Maia.; Simmons, Daimon P.; Ramirez, Christopher E.; Bedard, Melissa.; Fink, Catherine.; Ko, Jina.; León Peralta, Esmarline J.; Watts, Gerald.; Gomez-Rivas, Emma.; Davis, Vannessa.; Barilla, Rocky M.; Wang, Jianing.; Cunin, Pierre.; Bates, Samuel.; Morrison-Smith, Chevaun.; Nicholson, Benjamin.; Wong, Edmond.; El-Mufti, Leena.; Kann, Michael.; Bolling, Anna.; Fortin, Brooke.; Ventresca, Hayden.; Zhou, Wen.; Pardo, Santiago.; Kwock, Megan.; Hazra, Aditi.; Cheng, Leo.; Ahmad, Q. Rushdy.; Toombs, James A.; Larson, Rebecca.; Pleskow, Haley.; Luo, Nell Meosky.; Samaha, Christina.; Pandya, Unnati M.; Silva, Pushpamali.; Zhou, Sally.; Ganhadeiro, Zakary.; Yohannes, Sara.; Gay, Rakiesha.; Slavik, Jacqueline.; Mukerji, Shibani S.; Jarolim, Petr.; Walt, David R.; Carlyle, Becky C.; Ritterhouse, Lauren L.; Suliman, Sara. (Tufts University. Tisch Library., 2021)
Keywords: SARS-CoV-2, Coronavirus, COVID-19, Antibodies, Lateral flow assays.; Springer Open.